2019
DOI: 10.1111/acel.13046
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐134‐5p inhibition rescues long‐term plasticity and synaptic tagging/capture in an Aβ(1–42)‐induced model of Alzheimer’s disease

Abstract: Progressive memory loss is one of the most common characteristics of Alzheimer's disease (AD), which has been shown to be caused by several factors including accumulation of amyloid β peptide (Aβ) plaques and neurofibrillary tangles. Synaptic plasticity and associative plasticity, the cellular basis of memory, are impaired in AD.Recent studies suggest a functional relevance of microRNAs (miRNAs) in regulating plasticity changes in AD, as their differential expressions were reported in many AD brain regions. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…BDNF is able to relieve the inhibition of LIM kinase 1 translation, and in this manner contribute to synaptic development, maturation and/or plasticity [ 56 ]. Recently, Baby et al [ 57 ] found that miR-134 mediates post-transcriptional regulation of CREB1 and BDNF, as previously described by Gao et al [ 58 ], who demonstrated that mutant mice lacking Sirtuin 1 (SIRT1) catalytic activity shows reduction in both CREB and BDNF proteins and upregulation of miR-134. Thus, higher levels of miR-134 negatively regulate synaptic plasticity [ 58 ].…”
Section: The Human Bdnf Gene: Transcripts and Variantsmentioning
confidence: 76%
“…BDNF is able to relieve the inhibition of LIM kinase 1 translation, and in this manner contribute to synaptic development, maturation and/or plasticity [ 56 ]. Recently, Baby et al [ 57 ] found that miR-134 mediates post-transcriptional regulation of CREB1 and BDNF, as previously described by Gao et al [ 58 ], who demonstrated that mutant mice lacking Sirtuin 1 (SIRT1) catalytic activity shows reduction in both CREB and BDNF proteins and upregulation of miR-134. Thus, higher levels of miR-134 negatively regulate synaptic plasticity [ 58 ].…”
Section: The Human Bdnf Gene: Transcripts and Variantsmentioning
confidence: 76%
“…Gao and co-workers [ 39 ] reported that miR-134 mediates late long term potentiation (LTP) and synaptic plasticity through the Sirtuin1- cAMP-response-element binding protein (CREB) and brain-derived neurotrophic factor (BDNF) pathway in the hippocampus. miR‐134 post‐transcriptionally regulates the expression of CREB and BDNF in AD cases [ 40 ]. CREB and BDNF are two important plasticity-related proteins that are involved in synaptic plasticity and memory formation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is now considerable evidence that the dysregulation of miRNAs correlates with the progression and severity of AD [ 78 ]. The differential expression of miRNAs has been reported in many brain regions [ 79 ]. miRNAs can also regulate synaptic transmission and plasticity in the hippocampus and neocortex and regulate memory formation [ 80 ].…”
Section: Main Textmentioning
confidence: 99%
“…Research has further confirmed that genetic deletion of miR-132 in mice promotes A β deposition, leading to impaired memory and enhanced Tau pathology [ 81 ]. However, the upregulation of miR-142-5p and miR-134-5p expression contributes to the pathogenesis of AD by triggering synaptic dysfunction associated with A β -mediated pathophysiology [ 79 , 82 ]. In learning memory aspects, miR-124 and miR-181a, which are two miRNAs that are upregulated in the hippocampus, are directly associated with deficits in synaptic plasticity [ 83 , 84 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation